Research status of polycystic ovary syndrome treatment: a mini review and a bibliometric analysis from 2010 to 2023 - Yu-Xin Jin; Hang-Qi Hu; Jia-Cheng Zhang; Xi-Yan Xin; Yu-Tian Zhu; Hao-Lin Zhang; Rui-Wen Fan; Yang Ye; Dong Li (Gynecological Endocrinology)
Background Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder in premenopausal women, often linked to abdominal obesity, insulin resistance, and metabolic issues. With its heterogeneous nature, PCOS treatment should be tailored to individual symptoms and patient preferences. This study examines collaboration networks among countries, institutions, authors, references, and journals related to PCOS treatment.Methods Web of Science data was analyzed using VOSviewer and CiteSpace for bibliometric visualization. Chinese and Western medicine treatments for PCOS were reviewed, emphasizing symptom-targeted solutions.Results Data from 4682 records authored by 400 individuals from 515 institutes in 62 countries revealed China as the leading contributor. Notable authors include Monash University and Richard S. Legro. Common research themes include adipocytes, inflammation, insulin sensitivity, oxidative stress, and the gut microbiome. Tailoring treatment to individual needs is essential, focusing on hyperandrogenism, ovulation, and insulin resistance, with lifestyle counseling to address obesity.Conclusion This bibliometric analysis provides valuable insights into the research status of PCOS treatment. China has made significant contributions, and complementary and alternative therapies, such as traditional Chinese medicine and acupuncture, have also shown beneficial effects recently. The research on inflammation, oxidative stress, and the gut microbiome may provide new targets and strategies for the treatment of PCOS. The recognition of the metabolic problems in PCOS patients facilitates the formulation of more personalized treatment plans to improve the prognosis of patients.